(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the reality of screening and assessing nutritional status at the Pediatrics Department of Bach Mai hospital. Methods: Design of a before-after comparison study, on a sample of 200 pediatric patients from medical records from June to November 2020. Results: Pediatric patients recorded full weight, height within 36 hours after admission increased by 8.5% after improvement. The number of children who recorded weight and height before improvement was 108, corresponding to 54.5%. The number after improvement is 195 children, corresponding to 97.5%, higher than before improvement is 43%. The percentage of patients who achieved a 1-week reduction in food intake was recorded at a higher rate of 19.5%. On the medical records, the medical staff recorded and weighed the children: before the improvement was 150 medical records, corresponding to 75%, after the improvement, 187 medical records corresponding to 93.5%, 18.5% higher than before improvement. The percentage of children who were screened to assess their nutritional status after performing the improved research increased to over 90%. Conclusion: Screening sheet to assess nutritional status for inpatient pediatric patients applied at the Pediatrics Department of Bach Mai Hospital to improve nutritional status. Medical staff follow the form with full information according to the screening sheet, effective nutrition intervention for inpatient pediatric patients. The percentage of pediatric patients who were screened to assess their nutritional status after improving their nutritional status increased to over 90% after implementing the Nutrition Status Screening Sheet.